PENERAPAN GROOMING STANDARD PRAMUSAJI SEBAGAI BAGIAN DARI EXCELLENCE SERVICE DI DEPARTEMEN BANQUET HOTEL JW MARRIOTT MEDAN - Tambunan, Lyandru Togu Mulia; Sitanggang, Robby Arnestha; Tambunan, Ivan Benedict (Jurnal Ilmiah Akomodasi Agung, 2024)
The Implementation of Grooming Standard for Banquet Waiter as a crucial part for Excellence Service in JW Marriott Medan – Grooming plays a pivotal role in maintaining exceptional hotel service standards. For a Banquet Waiter, grooming is not just about looking neat; it’s about creating an unforgettable guest experience. Good grooming isn’t just about appearance; it’s also about hygiene. Consistent grooming reflects a Waiter’s commitment to their job. Service excellence is about going beyond your customer’s basic needs and exceeding their expectations. Customers are at the very heart of hospitality, making excellence in customer service an even more important focus in the hospitality industry. Hotels, restaurants, and tourism companies are unlikely to succeed without happy customers. The author will defining the grooming as a part of achieving excellence service in hotel operational. This paper is to study further implementation of Grooming Standard in order to achieve excellence service in Banquet operational. Study method using Qualitative Descriptive data, in order to study the object directly. Population data for this subject is 7 people concists of 2 supervisor, 1 wedding butler, 2 audio visual captain, and 2 banquet waiters. From the results of the discussion reviewed in the field, the results of our research at the JW Marriott Hotel Medan about the application of standardsgrooming employees is still not running according to the SOP that has beendetermined, the obstacle found is that there are still many waitresses who are not obey grooming standards such as the prohibition of Mustaches for men, the application ofEmployee hygiene as part of grooming standards at JW Marriott Hotels Medan needs to be developed so that every waitress understands whatbecome duties and responsibilities. The suggestions given by the author arethe hotel should provide or provide the latest uniform such as a t-shirt especially in the banquet section to carry out preparation,Supervisors/managers further improve grooming inspections so that they do not violations from employees were found again and gave a firm reprimand to employees who do not comply with the rules.